Hiob i jego modlitwa: od pobożnych sloganów do mistyki - Tronina, Antoni (Verbum Vitae, 2012)
The Book of Job read in synchronic way shows the evolution of prayer of the biblical hero. This hero, in the course of painful experiences, undergoes metamorphosis and passes the subsequent stages when approaching God in his prayer. From a rebellion against God, through an anger and argument with God, the hero experiences a deep spiritual depression. Finally, he accepts with confidence God’s way of proceeding in life and in the rule over the world. The hero’s prayer constitutes a model of maturation in human encounter with God.